Setting the stage for criteria and indicators for Malaysia Garden Cities: Putrajaya Green City as a case study - Amat Ramsayaman,; Abdullah Mohd, (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
Malaysian Government has embarked greening initiative to urban landscapes by planting trees and shrubs. This is in line with ultimate moves to transform the country into a Garden Nation by the year 2020. The policy on landscape was focused to planting of trees and shrubs along roads, sidewalks, highways and rivers together with establishment of many nurseries. The image of garden nation would be materialized when all cities in the country become green cities that portray the garden image in their design and visual dimensions. For Malaysia, however, there are no criteria and indicators to be based on as fundamental basis for green cities. A study was conducted to develop a reliable set of criteria and indicators for an ideal, green city or garden city. Delphi method was adopted to solicit the opinion from 30 experts through a series of questionnaires. As a result, it was able to generate and identified 8 criteria and 42 indicators for an ideal Malaysian green city where the top three criteria selected were: (i) safe, healthy and beautiful living working environment, functional; (ii) integrated landscapes, and (iii) need for a physical master plan to include network of high quality plants, open spaces, parks and green areas throughout the city. Following this, stakeholders’ perceptions on the importance of the selected criteria for the Malaysian green city were assessed using the Importance Performance Analysis Procedure. When compared to the earlier results produced by the expert panels, consensus were achieved including the primary stakeholders, domestic tourists and foreign tourists. The stakeholders’ perceptions upon the performance of Putrajaya as one of Malaysian garden city were also assessed by using Importance Performance Analysis. A “Safe and Healthy” including the “Beautiful Living Working Environment” were found to be consistently in to keep up the good work quadrant. Meanwhile, adequate funding to support garden city program was consistently shown a low performance level. It being perceives that the status of Putrajaya as the administrative centre for Malaysian where public funding by design will always be allocated to support garden city related activities. The study also revealed that beautiful landscapes, gardens, parks and nature are the most important attractions in Putrajaya. Visitors placed green attraction more important than other attractions in their decision to visit Putrajaya. This indicated that green areas particularly her garden and park are considered as the brand that able to attract tourists to visit the city. Hence, Putrajaya could definitely be considered having achieved her objective as a green garden city. The generated criteria and indicators should be used as a standard or condition to be met and recognized as a green or garden city.